2021
DOI: 10.1098/rsbl.2021.0283
|View full text |Cite
|
Sign up to set email alerts
|

Colourful traits in female birds relate to individual condition, reproductive performance and male-mate preferences: a meta-analytic approach

Abstract: Colourful traits in females are suggested to have evolved and be maintained by sexual selection. Although several studies have evaluated this idea, support is still equivocal. Evidence has been compiled in reviews, and a handful of quantitative syntheses has explored cumulative support for the link between condition and specific colour traits in males and females. However, understanding the potential function of females' colourful traits in sexual communication has not been the primary focus of any of those pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 83 publications
4
29
1
Order By: Relevance
“…Feather color is an important trait of poultry, and integumentary pigmentation produces a variety of plumage phenotypes, which plays an essential role in camouflage, sexual selection, communication, and thermoregulation in vertebrates (Si et al, 2021). Feather color is related to reproductive traits and is easy to observe, so it can be used as a genetic marker to play a crucial role in determining the genetic relationships among the breeds and fostering high‐quality breeds (Doutrelant et al, 2008; Hernández et al, 2021). Feather color is a qualitative trait regulated by multiple gene loci.…”
Section: Figurementioning
confidence: 99%
“…Feather color is an important trait of poultry, and integumentary pigmentation produces a variety of plumage phenotypes, which plays an essential role in camouflage, sexual selection, communication, and thermoregulation in vertebrates (Si et al, 2021). Feather color is related to reproductive traits and is easy to observe, so it can be used as a genetic marker to play a crucial role in determining the genetic relationships among the breeds and fostering high‐quality breeds (Doutrelant et al, 2008; Hernández et al, 2021). Feather color is a qualitative trait regulated by multiple gene loci.…”
Section: Figurementioning
confidence: 99%
“…There are two major classes of explanation for conspicuous female ornaments. The first is that ornaments are advantageous to females, through one or more of inter‐sexual, intra‐sexual, or social selection (Hernández et al, 2021 ). The second, which was essentially the default explanation for decades and is sometimes known as the genetic correlation or correlated response hypothesis, is that female ornaments evolve as a response to selection on males, owing to shared genetic underpinnings (Hare & Simmons, 2019 ; Kraaijeveld, 2014 ; Lande, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this explanation is often applied to male ornamentation, not only males but also females possess ornamentation. Recent phylogenetic and experimental studies have revealed that the correlated response hypothesis, i.e., intersexual genetic correlation with male ornamentation, alone cannot explain female ornamentation (e.g., Dale et al 2015), and that female ornamentation would evolve and be maintained due to its function in social interactions (reviewed in Amundsen & Pärn 2006; Kraaijeveld et al 2007; Tobias et al 2012; Hare & Simmons 2019; Hernandez et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is also the case even when female ornamentation is experimentally manipulated, because ornamentation feeds back to physiological state (e.g., Vitousek et al 2013) and behavior (e.g., ornamentation and its manipulation may affect general and mating activity; e.g., Barnald 1990; Balmford & Thomas 1992; Wolf et al 2004), which confounds indirect (and even direct) measures of male mate preference. Male mate preference on female ornamentation measured by male behavior while controlling for these confounding factors, for example, using model presentation experiments, provides direct evidence of male mate preference, though only a handful studies are reported (e.g., Jones & Hunter 1999; reviewed in Amundsen & Pärn 2006; Hernandez et al 2021).…”
Section: Introductionmentioning
confidence: 99%